UPAYA PENINGKATAN SUMBER DAYA MANUSIA MELALUI BIMBINGAN BELAJAR DAN MENINGKATKAN KETERAMPILAN SISWA ANAK-ANAK SD - Sulis Setianingrum (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Community service activities carried out in the village of Nanggerang Jaya Mandirancan. Community service activities are carried out based on the identification of problems found in Nanggerang Jaya Village. The main problem is about education. The solution to the existing problem is to conduct tutoring activities and improve elementary school student skills. Keywords: tutoring, community engagement, education.